Protective effect of Qingre Huoxue decoction against myocardial infarction via PI3K/Akt autophagy pathway based on UPLC-MS, network pharmacology, and in vivo evidence - Zheng Jin; Wenbo Zhang; Yuan Luo; Xiushen Li; Lijin Qing; Qiang Zuo; Junfeng Fang; Wei Wu (Taylor & Francis Group, 2021)
Context Qingre Huoxue (QRHX) decoction, a traditional Chinese medicine, has been widely used to prevent and treat myocardial infarction (MI). Objective This study elucidates the possible mechanisms of QRHX in preventing or treating MI in a rat model. Materials and methods The chemical constituents of QRHX were identified by UPLC-MS. Sprague-Dawley rats were randomly divided into the Sham (normal saline), Model (normal saline), QRHX-L, QRHX-M and QRHX-H group (n = 10 per group). QRHX decoction was administered by gavage to the rats for 14 days (5, 10 and 20 g/kg/day). The left anterior descending ligation method was performed to develop MI in Model and QRHX groups, and the same surgical procedures excluding ligation sutures were performed for the sham group. Finally, we evaluated cardiac function, myocardial fibrosis degree, serum inflammatory factors, autophagy levels and verified the signalling pathways in vivo. Results A total of 68 active components of QRHX corresponding to 223 active targets were obtained and 2558 MI-related disease targets were collected. After integration, 123 QRHX anti-MI targets were obtained, and 70 signalling pathways, such as PI3K/Akt, were identified by enrichment analysis. In vivo experiments suggest that QRHX could reduce the degree of myocardial fibrosis, downregulate serum inflammatory factors, and promote autophagy in MI rats. Discussion and Conclusions QRHX plays a protective role in the myocardium by mediating PI3K/Akt signalling pathway to activate autophagy and inhibiting inflammatory factor expression. These findings provide a scientific basis for further research and validation of QRHX as a potential therapeutic for MI.